A review of human cornea finite element modeling: geometry modeling, constitutive modeling, and outlooks - Pang, Guobao; Wang, Chenyan; Wang, Xiaojun; Li, Xiaona; Meng, Qiaoyu (Frontiers in Bioengineering and Biotechnology, 2024)
The cornea is a vital tissue of the human body. The health status of the cornea has a great impact on the quality life of person. There has been a great deal of research on the human cornea biomechancis.However, the difficulty in obtaining the human cornea has greatly limited the research of cornea biomechancis . Using finite element modelling has become a very effective and economical means for studying mechanical properties of human cornea. In this review, the geometrical and constitutive models of the cornea are summarised and analysed, respectively. Some factors affecting of the finite element calculation are discussed. In addition, prospects and challenges for the finite element model of the human cornea are presented. This review will be helpful to researchers performing studies in the relevant fields of human cornea finite element analysis.